Studi Masyarakat Islam Kepulauan di Maluku Utara; Suatu Perspektif Interdisipliner - Bujang, Agus Salim; Wajo, Abd. Rauf (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research investigates the Study of Island Muslim Communities (SMIK) in North Maluku through an interdisciplinary perspective, aiming to develop a comprehensive methodological framework for understanding the complexity of island societies. The study employs a qualitative approach utilizing theoretical analysis and literature review, drawing from scholarly works by researchers such as Wallace, Malinowski, Fox, and conceptual insights from Baldacchino, Eickelman, and other experts.The geographical context of North Maluku, characterized by 805 verified islands with only 82 inhabited, forms the research's spatial foundation. The study identifies three primary epistemological approaches—positivism, interpretivism, and critical social science—to analyze island communities. An interdisciplinary methodology is applied to comprehend the socio-cultural, ecological, and religious dynamics of Muslim populations in the archipelagic region.Research findings reveal that SMIK is not a standalone academic discipline but rather a cross-disciplinary research focus integrating socio-cultural, ecological, religious, and historical-empirical perspectives. The conceptualization of "Island Muslim Communities" emerges by considering physical environmental characteristics, social-cultural diversity, and religious practices within specific contextual frameworks.The research contributes to methodological development by emphasizing local Islamic expression variations (islams) and the intricate human-environment interactions in archipelagic settings. Future research recommendations include developing integrative methodological models, exploring local contexts, and analyzing the socio-religious dimensions of island communities